1978
DOI: 10.1002/mrc.1270111012
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopie RMN du Carbone‐13 de Thiocétones Aliphatiques: Propanethione et Dérivés, Thiocétones Bicycliques et α Cyclopropaniques

Abstract: Carbon-13 N M R spectra of various aliphatic ketones and tbioketones were determined and interpreted. As shown by the relation between OC chemical sbifts in C=A groups, the C=S is more sensitive to the substituents than the C=O group. Conjugative effects are more pronounced in a-cyclopropyl thioketones than in a-cydopropyl ketones. Compte tenu des remarques suivantes nous avons tent6 de relier So, S, et o, en restant conscient de ce que, en skrie cktonique, les variations AE ont une part non nkgligeable dans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Statistical analysis of all the compounds of Group I1 yields Eqn (5) (correlation coefficient 0.9925 and standard error 3.8), which can be compared with Eqn (2). 6(C=S) = 1.53 6(C=O) -63.2 (5) The C=O vs C=S shifts of the ureas and thioureas 2426 ( Table 1) would be expected to be linearly related, in view of Kalinowski's and Kessler's work,3 which interpreted this correlation mainly in terms of the mean excitation energy in the paramagnetic screening term.3…”
Section: (4)mentioning
confidence: 98%
“…Statistical analysis of all the compounds of Group I1 yields Eqn (5) (correlation coefficient 0.9925 and standard error 3.8), which can be compared with Eqn (2). 6(C=S) = 1.53 6(C=O) -63.2 (5) The C=O vs C=S shifts of the ureas and thioureas 2426 ( Table 1) would be expected to be linearly related, in view of Kalinowski's and Kessler's work,3 which interpreted this correlation mainly in terms of the mean excitation energy in the paramagnetic screening term.3…”
Section: (4)mentioning
confidence: 98%
“…Andreiu et al . () identified a variety of chemical shifts on carbon‐13 NMR spectra for an array of aliphatic ketones and thioketones and assigned thioketone values to be in the range of 35–41 ppm that well falls in line with the present datum (37.5 ppm). It is an established fact that alkanes resonate well between 11 and 25 ppm on the basis of differences in substitutions and the present investigation proves a characteristic alkane signal at 20.1 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…[94] Even though the free thiosalen ligand is not accessible, Bergman et al were able to crystalize and characterize the methyl ketimine analog. However, it has also been reported that the influence of substituents on this resonance is more pronounced [96] and that the C Ar S resonance is a rather bad probe for the evaluation of electronic structures. The even larger low-field shift of this signal in H 3 S 3 can therefore be interpreted as an even stronger contribution of the thione-enamine resonance structure VIII in H 3 S 3 .…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The even larger low-field shift of this signal in H 3 S 3 can therefore be interpreted as an even stronger contribution of the thione-enamine resonance structure VIII in H 3 S 3 . However, it has also been reported that the influence of substituents on this resonance is more pronounced [96] and that the C Ar S resonance is a rather bad probe for the evaluation of electronic structures.…”
Section: Heteroradialene Character In Extended Thiophloroglucinol Ligmentioning
confidence: 99%